PROPORTION OF HBsAg AND HBeAg POSITIVE IN MATERNAL PATIENTS AND THEIR HBsAg POSITIVES BABIES WITH IMMUNOPROPHYLAXIS OF HBV IMMUNIZATION IN Dr. SOETOMO GENERAL HOSPITAL, SURABAYA - Tanadi, Melina Rosita; Lusida, Maria Inge; Joewono, Hermanto Tri (Institute of Topical Disease Universitas Airlangga, 2017)
Hepatitis B Virus (HBV) can be transmitted vertically from mother to her baby. Mothers with HBsAg and HBeAg positives have more risk of transmitting HBV to her baby rather than HBsAg positives only. The aim of this study is to determine the proportion of maternal patient with HBsAg and HBeAg positives and their HBsAg positives babies with immunoprophylaxis of HBV immunization. This study was performed by analytical observation using medical records in 2013-2014 at Obstetric and Gyn ecology Department, Dr. Soetomo Hospital. The samples were all maternal patients (3796) during that period and also their babies from HBsAg positives mothers. Unfortunately, several original medical records were not available. Thirty two (0,85%) out of 3781 maternal patients were found to be HBsAg positives, and three (9,37%) of 32 patients with HBsAg positives were HBeAg positives. From 32 mothers who were positive HBsAg, 22 complete medical records of their babies were found and all of them (100%) had been given Hepatitis B Immunoglobulin (HBIG) and hepatitis B vaccine less than twelve hours after birth. In three cases of the babies from HBeAg positives mothers which had been given prophylaxis properly, two cases each of which was with caesarean and spontaneous delivery were HBsAg negatives. Interestingly, the other one which born with spontaneous delivery was found to be HBsAg positives. Further study in this HBsAg positives baby, especially in analyzing its HBV DNA is needed. The epidemiology of hepatitis B in maternal patients, especially that with complete and neat data needs further research.